2019
DOI: 10.3390/ijms20051158
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Reactive Oxygen Species (ROS) in Indirubin Derivative-Induced Cell Death in Cutaneous T-Cell Lymphoma Cells

Abstract: Cutaneous T-cell lymphoma (CTCL) may develop a highly malignant phenotype in its late phase, and patients may profit from innovative therapies. The plant extract indirubin and its chemical derivatives represent new and promising antitumor strategies. This first report on the effects of an indirubin derivative in CTCL cells shows a strong decrease of cell proliferation and cell viability as well as an induction of apoptosis, suggesting indirubin derivatives for therapy of CTCL. As concerning the mode of activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The extrinsic apoptosis pathway is negatively regulated by antagonistic proteins. Thus, c-FLIP (cellular FLICE-inhibitory protein) serves as a competitive inhibitor of caspase-8/-10; it can bind to the DISC but does not promote effector caspase activation [23,24]. Further downstream, the family of cellular inhibitor of apoptosis proteins (cIAPs) can bind to effector caspases and thus prevent their proteolytic activity [25,26] (Figure 2).…”
Section: Induction Of Apoptosis By Death Ligandsmentioning
confidence: 99%
“…The extrinsic apoptosis pathway is negatively regulated by antagonistic proteins. Thus, c-FLIP (cellular FLICE-inhibitory protein) serves as a competitive inhibitor of caspase-8/-10; it can bind to the DISC but does not promote effector caspase activation [23,24]. Further downstream, the family of cellular inhibitor of apoptosis proteins (cIAPs) can bind to effector caspases and thus prevent their proteolytic activity [25,26] (Figure 2).…”
Section: Induction Of Apoptosis By Death Ligandsmentioning
confidence: 99%
“…Recent studies showed that indirubin derivatives DKP-071 and DKP-073 can activate the apoptotic pathway in cutaneous T-cell lymphoma and melanoma cells by inducing the production of reactive oxygen species (ROS) (Soltan et al, 2019;Zhivkova et al, 2019). Oxidative stress and elevation of ROS induced by chemicals have pleiotropic deleterious effects including developmental toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although detrimental in nature, but few studies of their beneficial effects have been reported. ROS appeared to play an important role in proapoptotic pathway in Cutaneous T-cell lymphoma (CTCL) when treated with the indirubin derivative DKP-071 ( Soltan et al., 2019 ). In a search for newer antitumor strategy, a sharp decrease in cell proliferation and cell viability was observed with DKP-071.…”
Section: Introductionmentioning
confidence: 99%